Dendrobium Nobile Lindl. Alkaloid Suppresses NLRP3-Mediated Pyroptosis to Alleviate LPS-Induced Neurotoxicity - Dai-Di Li; Dai-Di Li; Hong-Xia Fan; Rong Yang; Ying-Ying Li; Feng Zhang; Jing-Shan Shi; Jing-Shan Shi (Frontiers Media S.A., 2022)
Alzheimer's disease (AD) is a neurodegenerative disorder recognized as a global public health priority. Although available treatments temporarily relieve the symptoms, they could not prevent the progression of cognitive decline. Natural compounds have been rich sources for drug discovery. Dendrobium nobile Lindl. alkaloid (DNLA) is the main active compound in Dendrobium nobile Lindl, a traditional Chinese herbal medicine. Recent studies indicated that DNLA produced neuroprotection. However, the mechanisms underlying DNLA-generated neuroprotection remain unknown. To investigate neuroprotection and the underlying mechanisms of DNLA, mouse hippocampus injection of lipopolysaccharide (LPS)-induced neuronal damage was performed. DNLA protected hippocampus neurons and working memory disorder against LPS-induced neurotoxicity. In addition, DNLA suppressed cell undergoing membrane lysis and cell swelling and inhibited the essential mediator of pyroptosis GSDMD-N expressions. Furthermore, DNLA-mediated neuroprotection was dependent on the inhibition of NLRP3 inflammasome activation, as evidenced by the fact that DNLA reduced pro-inflammatory factor (IL-18 and IL-1β) production and inhibited the expression of related proteins. DNLA-exerted neuroprotection against LPS-induced neuronal damage, and cognitive impairment was not observed in NLRP3 knockout mice. Together, this study suggested that DNLA attenuated NLRP3-mediated pyroptosis to generate neuroprotection against LPS-induced neuronal damage and cognitive impairment.